Effects of Depolarization Field and Interfacial Coupling on the Polarization of Ferroelectric Bilayers - 郑朝丹 张端明 刘心明 杨斌 刘超军 于军 (Chinese physics letters, 2010)
A ferroelectric bilayer model considering depolarization field and interfacial coupling is proposed and the expression of the depolarization field is derived. The spatial profiles of spontaneous polarization and hysteresis loops are calculated using the numerical method with and without considering the depolarization field. The effects of the depolarization field and interfacial coupling on the polarization of second-order ferroelectric bilayers are studied systematically. When interfacial coupling is ferroelectric coupling, the interface spontaneous polarization increases and the area of hysteresis loop becomes larger with increasing coupling. When interfacial coupling is antiferroelectric coupling, the depolarization field makes the central loop become smaller and the shape of the hysteresis loop becomes steep. Meanwhile, as interfacial coupling increases, the outer loops stretch further out horizontally and the size of the central loop widens.